GE_GERICHTE C/25199/2013 vom 2. Februar 2015 - GE Cour de justice (2015)
BAIL À LOYER; MAXIME INQUISITOIRE; DROIT À LA PREUVE; DIMINUTION DE LOYER; BRUIT | CPC.247.2.b.1; aCO.274d.3; CO.256.1; CO.259d